2020
DOI: 10.1590/1413-81232020251.28952019
|View full text |Cite
|
Sign up to set email alerts
|

Desafios na formação de enfermeiros indígenas em Mato Grosso, Brasil

Abstract: Resumo A formação do enfermeiro no Brasil, ainda se apresenta como um desafio para as universidades, face as diversidades étnicas e as particularidades regionais existentes. Assim, o objetivo do estudo foi identificar os desafios no processo de formação de enfermeiros indígenas em Mato Grosso, Brasil. Trata-se de estudo exploratório e qualitativo, junto a 11 enfermeiros indígenas. A análise dos dados, baseou-se na interculturalidade de Paulo Freire. Verificou-se que todos participantes, buscam a integração dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
0
5
0
5
Order By: Relevance
“…The inclusion of indigenous people and quilombolas based on affirmative action makes it possible for access to the university to be possible, but not necessarily equitable (4) . Therefore, the need for student selection and initiatives to adhere to initiation to research and extension through academic projects.…”
Section: Moment 1 -Collaborative Processes and Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of indigenous people and quilombolas based on affirmative action makes it possible for access to the university to be possible, but not necessarily equitable (4) . Therefore, the need for student selection and initiatives to adhere to initiation to research and extension through academic projects.…”
Section: Moment 1 -Collaborative Processes and Flowsmentioning
confidence: 99%
“…Regarding the training of health professionals who have identity related to native and Afro-descendant populations and the involvement of different institutions, there is a lack of information. It is noted, in the few studies identified, that, due to the historical processes, there are disadvantages in the course of teaching-learning of these groups (4) . Therefore, there is a need to record institutions' experiences, in order to contribute to an inclusive education in nursing and health.…”
Section: Introductionmentioning
confidence: 99%
“…Para Nascimento et al (2019), a equipe de enfermagem desenvolve junto à essa população um trabalho que se baseia no respeito à cultura e tradições, fortalecendo os vínculos entre profissionais de saúde e lideranças da comunidade indígena.…”
Section: Ações Dos Profissionais De Saúde No Território Indígenaunclassified
“…The training of Indigenous nurses could contribute to overcoming the cultural “barriers” that frequently limit effective intercultural nursing performance. However, it is not enough for a student to be Indigenous; training programs require structuring according to the educational agenda of transcultural health service [ 55 , 56 , 57 ]. It is important to emphasize that even Indigenous nurses working in community health posts participate in intercultural or transcultural contexts, as they navigate the dynamic frontiers between Indigenous and biomedical health practices, beliefs, and practices.…”
Section: Intercultural Education and Training Of Primary Health Care Nurses Working With Indigenous Peoplesmentioning
confidence: 99%
“…This is because professors are not prepared for teaching nursing from a transcultural perspective and schools lack pedagogical approaches that adequately contemplate students’ diverse historical, sociocultural, environmental, and political backgrounds. Thus, hegemonic biomedical practices predominate while traditional medical systems and ethnomedicine are relegated to a secondary level [ 55 , 56 , 57 ].…”
Section: Intercultural Education and Training Of Primary Health Care Nurses Working With Indigenous Peoplesmentioning
confidence: 99%